Correlation Between Cholinesterase Enzyme Levels and Leukocyte Differential Count in Farmers Exposed to Pesticides - Rochmad Agung Purnomo; Alya Sabrina Putri Kalista; Ameilisa Eka Nurriani; Septiani Tri Wulandhari; Mastuti Widi Lestari (Jurnal Biologi Tropis, 2026)
Pesticide exposure in farmers has the potential to cause health problems, one of which indicated by decreased cholinesterase enzyme levels and changes in the leukocyte profile as part of the immune response. This study aimed to determine the correlation between cholinesterase enzyme levels and leukocyte differential count, including eosinophils, lymphocytes, monocytes, and neutrophils, among vegetable farmers exposed to pesticides in Matesih Village, Matesih District. The study used an observational analytical design with a cross-sectional approach. The study population consisted of 29 male vegetable farmers, from which 22 respondents were selected via purposive sampling based on specific inclusion criteria. Cholinesterase enzyme levels were measured using the Cobas Integra 400 Plus photometric method, while leukocyte differential counts were analyzed flow cytometry with tri-angle laser scatter on the Mindray BC-5130 hematology analyzer. Data analysis was performed using Pearson and Spearman correlation tests adjusted to the distribution of the study data. The results showed that most respondents had cholinesterase enzyme levels that were still within the normal range. The correlation analysis indicated no significant correlation between cholinesterase enzyme levels and leukocyte differential count (eosinophils, lymphocytes, monocytes, or neutrophils) (p > 0.05).